Search for doubly charged higgs boson pair production in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Arov, M.; et al. (American Physical Society (APS), 2012)
We present a search for pair production of doubly charged Higgs bosons in the processes qq̄→H ++H - decaying through H ±±→τ ±τ ±,μ ±τ ±, μ ±μ ±. The search is performed in pp̄ collisions at a center-of-mass energy of √s=1.96TeV using an integrated luminosity of up to 7.0fb -1 collected by the D0 experiment at the Fermilab Tevatron Collider. The results are used to set 95 C.L. limits on the pair production cross section of doubly charged Higgs bosons and on their mass for different H ±± branching fractions. Models predicting different H ±± decays are investigated. Assuming B(H ±±→τ ±τ ±)=1 yields an observed (expected) lower limit on the mass of a left-handed HL±± boson of 128 (116) GeV and assuming B(H ±±→μ ±τ ±)=1 the corresponding limits are 144 (149) GeV. In a model with B(H ±±→τ ±τ ±)=B(H ± ±→μ ±τ ±)= B(H ±±→μ ±μ ±)=1/3, we obtain M(HL±±)>130(138)GeV. © 2012 American Physical Society.